The pathogenesis of scleroderma - Latika Gupta; Sakir Ahmed; Abhishek Zanwar (Indian Journal of Rheumatology)
Systemic sclerosis (SSc) results from the complex interplay between the immune system, vasculature and tissue-repair mechanisms. Endothelial injury is the prime event; environmental triggers in the susceptible individual trigger the pathologic process, which translates into fibrosis. The outcome of SSc is not as bleak as it looked a couple of decades ago. With a greater understanding of older pathways, as well as elucidation of newer ones, the potential targets to block and even reverse fibrosis bring around a revolution in the way we look at this once dreaded disease.